High-load electrode material and preparation method thereof

By reacting 4,4'-diaminodiphenyldisulfide with phenol and other raw materials in the electrode material to form an azo structure, and combining epoxy chlorohydrin and sodium hydroxide to form a modified monomer, the low load of the electrode material is solved. and the problem of performance degradation has achieved an improvement in capacity retention rate after high load and multiple cycles.

CN119252676AInactive Publication Date: 2025-01-03ANHUI YONGZHUO CABLE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411777692.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

At this stage, the electrode material load is low and performance deteriorates after multiple cycles.

Method used

By reacting 4,4'-diaminodiphenyldisulfide with phenol and other raw materials to form an azo structure, combining epoxy chlorohydrin and sodium hydroxide to form a modified monomer, and with 4,4'4'-triamino group Trianiline reacts with 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, adds a modified filler, and after high-temperature imidation treatment, a high-load electrode material is formed. The modified filler forms a metal organic through dehydration reaction. Framework, increase power storage capacity and improve lithium storage performance.

Benefits of technology

The preparation of high-load electrode materials is realized. The porous mesh structure of the modified filler and the internal metal oxide support improve capacitance performance. The organic matter on the surface contains N=N bonds and S-S bonds to increase lithium storage performance and extend the electrode material. cyclic stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-load electrode material and a preparation method thereof, and the high-load electrode material is prepared by the following steps: reacting a modified monomer, 4, 4 ', 4'-triaminotriphenylamine and 3, 3 ', 4, 4'-biphenyl tetracarboxylic dianhydride to form polyamic acid, adding a modified filler, reacting amino on the modified filler with part of carboxyl on the polyamic acid, and carrying out high-temperature imidization treatment. The surface of the modified filler contains amino groups which can react with a polyamide acid molecular chain, the molecular chain is of a hyperbranched structure, so that the electrolytic material is an interlaced porous grid, the specific surface of the electrolytic material is increased, the modified filler internally contains a structure in which silicon and carbon support each other, and the surface of the modified filler is coated with organic polymers, so that collapse and expansion of the electrode material are prevented, and the service life of the electrode material is prolonged. The electrode material has the advantages that the electrode material contains metal oxide inside to form pseudocapacitance to increase the electricity storage capacity, the organic matter on the surface contains N = N bonds and S-S bonds to improve the lithium storage performance, and the capacity of the electrode material is further increased due to the addition of 4, 4 '4' '-triaminotriphenylamine and a large number of benzene ring structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode material preparation, and in particular to a high-load electrode material and a preparation method thereof. Background Art

[0002] The rapid progress of industry and society has led to a sharp increase in energy demand, while traditional fossil energy is facing a shortage dilemma. In addition, the environmental hazards caused by the combustion of fossil fuels such as coal and oil cannot be ignored. Therefore, in order to ensure the sustainable development of social economy, energy development has gradually turned to renewable green energy, such as wind energy, geothermal energy, solar energy and bioenergy. However, renewable energy currently has disadvantages such as high development cost, unstable energy supply, high storage technology and geographical restrictions, which limit its scope of application. Therefore, the key to coping with the problem of renewable energy transmission and storage is to develop high-energy and high-stability energy storage devices. Supercapacitors are mainly composed of current collectors, electrolytes, electrode materials, diaphragms and packaging materials. The most critical part that determines the performance of supercapacitors is the electrode material. The performance of the electrode material has a decisive influence on the charge storage capacity of the supercapacitor. Summary of the invention

[0003] The purpose of the present invention is to provide a high-load electrode material and a preparation method thereof, which solves the problem that the current electrode material has low load and performance degradation after multiple cycles.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high-load electrode material comprises the following steps: Step A1: dissolve 4,4'-diaminodiphenyl disulfide in anhydrous ethanol, add hydrochloric acid solution, stir and add sodium nitrite solution at a speed of 60-80 r / min and a temperature of 0-5°C, stir for 10-15 minutes, add phenol, react for 30-40 hours, adjust the pH value to neutral, heat to room temperature, and stir for 2-3 hours to obtain intermediate 1; Step A2: The intermediate 1, epichlorohydrin, benzyltriethylammonium chloride and DMF are mixed uniformly, and the mixture is reacted for 3-4 hours at a speed of 200-300 r / min, a temperature of 100-105° C. and nitrogen protection, and the mixture is cooled to 70-75° C., a sodium hydroxide solution is added, and the mixture is reacted for 15-20 hours to obtain the intermediate 2. The intermediate 2, ethylenediamine and DMF are mixed uniformly, and the mixture is reacted for 8-10 hours at a speed of 150-200 r / min, a temperature of 25-30° C. and a pH of 11-12 to obtain the modified monomer; Step A3: Evenly mix the modified monomer, 4,4'4''-triaminotriphenylamine and N-methylpyrrolidone, stir and add 3,3',4,4'-biphenyltetracarboxylic dianhydride at a speed of 120-150r / min, a temperature of 20-25°C and a nitrogen atmosphere, react for 20-25h, add the modified filler, continue stirring for 3-5h, heat to 180-185°C, react for 4-6h, and obtain a high-loading electrode material.

[0005] Furthermore, the amount ratio of 4,4'-diaminodiphenyl disulfide, hydrochloric acid solution, sodium nitrite solution and phenol in step A1 is 2mmol:10mL:5mL:4mmol, the mass fraction of hydrochloric acid solution is 8%, and the mass fraction of sodium nitrite solution is 5%.

[0006] Furthermore, the amount ratio of the intermediate 1, epichlorohydrin and sodium hydroxide solution described in step A2 is 40mmol:80mmol:10mL, the mass fraction of the sodium hydroxide solution is 30%, the amount of benzyltriethylammonium chloride is 1-3% of the sum of the mass of the intermediate 1 and epichlorohydrin, and the molar ratio of the intermediate 2 and ethylenediamine is n:n+1, where n is a natural number greater than 0.

[0007] Furthermore, the amount ratio of the modified monomer, 4,4'4''-triaminotriphenylamine, 3,3',4,4'-biphenyltetracarboxylic dianhydride and modified filler described in step A3 is 40mmol:20mmol:60mmol:1g.

[0008] Further, the modified filler is prepared by the following steps: Step B1: octaaminopropyl cage-type polysilsesquioxane, caffeic acid, dicyclohexylcarbodiimide and DMF are mixed evenly, and reacted at a speed of 150-200 r / min and a temperature of 30-40° C. for 5-7 hours to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, 5A molecular sieve and DMF are mixed evenly, and reacted at a speed of 120-150 r / min and a temperature of 60-65° C. for 10-15 hours to obtain intermediate 4; Step B2: The intermediate 4, o-phenylenediamine, potassium carbonate and DMF are mixed uniformly, reacted at a speed of 150-200 r / min and a temperature of 80-85° C. for 10-15 hours, and the pH value is adjusted to 5 to obtain the intermediate 5. The intermediate 5, cobalt nitrate hexahydrate, nickel nitrate hexahydrate and DMF are mixed uniformly, ultrasonically treated at a frequency of 20-30 kHz and a temperature of 20-25° C. for 30-40 minutes, and then allowed to stand for 7-9 hours to obtain the precursor; Step B3: Place the precursor in a tubular furnace, heat it to 800-900°C at a heating rate of 5-10°C in a nitrogen atmosphere, calcine for 4-6 hours, cool it to room temperature, disperse it in anhydrous ethanol, add 3-aminopropyltriethoxysilane and deionized water, react at a speed of 200-300r / min and a temperature of 50-60°C for 2-3 hours to obtain a modified filler.

[0009] Furthermore, the molar ratio of octaaminopropyl cage-type polysilsesquioxane, caffeic acid and dicyclohexylcarbodiimide described in step B1 is 1:8:8.2, and the usage ratio of the intermediate 3,4-formylphenylboronic acid and 5A molecular sieve is 2mmol:16mmol:2g.

[0010] Furthermore, the usage ratio of the intermediate 4, o-phenylenediamine and potassium carbonate in step B2 is 1 mmol:8 mmol:1 g, and the molar ratio of the intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 2:1:1.

[0011] Furthermore, the amount of 3-aminopropyltriethoxysilane used in step B3 is 1-3% of the mass of the precursor.

[0012] Beneficial effects of the present invention: A high-load electrode material prepared by the present invention uses 4,4'-diaminodiphenyl disulfide and phenol as raw materials to react to form an azo structure to obtain an intermediate 1, and the intermediate 1 is reacted with epichlorohydrin to make the phenolic hydroxyl group on the intermediate 1 react with the epoxy group on the epichlorohydrin, and then the ring is closed under the action of sodium hydroxide solution to form a new epoxy group to obtain a modified monomer, and the modified monomer, 4,4'4''-triaminotriphenylamine and 3,3',4,4'-biphenyltetracarboxylic dianhydride are reacted to form Polyamic acid is added with a modified filler, wherein the amino groups on the modified filler can react with part of the carboxyl groups on the polyamic acid, and a high-temperature imidization treatment is performed to obtain a high-load electrode material. The modified filler is made of octaaminopropyl cage-type polysilsesquioxane and caffeic acid as raw materials, and a dehydration reaction is performed under the action of dicyclohexylcarbodiimide, so that the amino groups on the octaaminopropyl cage-type polysilsesquioxane react with the carboxyl groups of caffeic acid to obtain an intermediate 3, and the intermediate 3 is reacted with 4-formylphenylboronic acid, so that the boronic acid group on the 4-formylphenylboronic acid reacts with the carboxyl group on the intermediate 3. The intermediate 4 is reacted with catechol to form a borate ester to obtain intermediate 4, and intermediate 4 is reacted with o-phenylenediamine so that the aldehyde group on intermediate 4 reacts with o-phenylenediamine to form an imidazole structure to obtain intermediate 5, and intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate are reacted to form a metal organic framework, which is then carbonized under a nitrogen atmosphere, and finally surface treated with 3-aminopropyltriethoxysilane to graft amino groups on the surface to obtain a modified filler, the surface of the modified filler contains amino groups that can react with the polyamic acid molecular chain, and the amic acid molecular chain is a hyperbranched structure, so that the electrolytic material is an interwoven porous grid, which increases its specific surface area, and the modified filler contains a structure in which silicon and carbon support each other, and the surface is coated with organic polymers, which prevents the collapse and expansion of the electrode material, contains metal oxides inside to form pseudocapacitance and thus increases the storage capacity, and the organic matter on the surface contains N=N bonds and SS bonds that can increase the lithium storage performance, and the addition of 4,4'4''-triaminotriphenylamine and a large number of benzene ring structures further increases the capacity of the electrode material. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0014] A method for preparing a high-load electrode material comprises the following steps: Step A1: 4,4'-diaminodiphenyl disulfide was dissolved in anhydrous ethanol, and hydrochloric acid solution was added. Under the conditions of a rotation speed of 60 r / min and a temperature of 0°C, sodium nitrite solution was added while stirring. After stirring for 10 minutes, phenol was added and the reaction was carried out for 30 hours. The pH value was adjusted to neutral, the temperature was raised to room temperature, and the mixture was stirred for 2 hours to obtain intermediate 1. Step A2: The intermediate 1, epichlorohydrin, benzyltriethylammonium chloride and DMF are mixed evenly, and the reaction is carried out for 3 hours at a speed of 200 r / min, a temperature of 100° C. and nitrogen protection, and the temperature is lowered to 70° C., and a sodium hydroxide solution is added, and the reaction is continued for 15 hours to obtain the intermediate 2. The intermediate 2, ethylenediamine and DMF are mixed evenly, and the reaction is carried out for 8 hours at a speed of 150 r / min, a temperature of 25° C. and a pH value of 11 to obtain the modified monomer; Step A3: Evenly mix the modified monomer, 4,4'4''-triaminotriphenylamine and N-methylpyrrolidone, stir and add 3,3',4,4'-biphenyltetracarboxylic dianhydride at a speed of 120 r / min, a temperature of 20°C and a nitrogen atmosphere, react for 20 hours, add the modified filler, continue stirring for 3 hours, heat to 180°C, react for 4 hours, and obtain a high-loading electrode material.

[0015] The amount ratio of 4,4'-diaminodiphenyl disulfide, hydrochloric acid solution, sodium nitrite solution and phenol described in step A1 is 2mmol:10mL:5mL:4mmol, the mass fraction of hydrochloric acid solution is 8%, and the mass fraction of sodium nitrite solution is 5%.

[0016] The amount ratio of intermediate 1, epichlorohydrin and sodium hydroxide solution described in step A2 is 40mmol:80mmol:10mL, the mass fraction of sodium hydroxide solution is 30%, the amount of benzyltriethylammonium chloride is 1-3% of the sum of the mass of intermediate 1 and epichlorohydrin, and the molar ratio of intermediate 2 and ethylenediamine is n:n+1, where n is a natural number greater than 0.

[0017] The amount ratio of the modified monomer, 4,4'4''-triaminotriphenylamine, 3,3',4,4'-biphenyltetracarboxylic dianhydride and modified filler described in step A3 is 40mmol:20mmol:60mmol:1g.

[0018] The modified filler is prepared by the following steps: Step B1: octaaminopropyl cage-type polysilsesquioxane, caffeic acid, dicyclohexylcarbodiimide and DMF were mixed evenly, and reacted at a speed of 150 r / min and a temperature of 30° C. for 5 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, 5A molecular sieve and DMF were mixed evenly, and reacted at a speed of 120 r / min and a temperature of 60° C. for 10 h to obtain intermediate 4; Step B2: The intermediate 4, o-phenylenediamine, potassium carbonate and DMF were mixed uniformly, reacted at a speed of 150 r / min and a temperature of 80° C. for 10 h, and the pH value was adjusted to 5 to obtain the intermediate 5. The intermediate 5, cobalt nitrate hexahydrate, nickel nitrate hexahydrate and DMF were mixed uniformly, ultrasonically treated at a frequency of 20 kHz and a temperature of 20° C. for 30 min, and then allowed to stand for 7 h to obtain the precursor; Step B3: Place the precursor in a tubular furnace, heat it to 800°C at a heating rate of 5°C in a nitrogen atmosphere, calcine for 4 hours, cool it to room temperature, disperse it in anhydrous ethanol, add 3-aminopropyltriethoxysilane and deionized water, react at a speed of 200 r / min and a temperature of 50°C for 2 hours to obtain a modified filler.

[0019] The molar ratio of octaaminopropyl cage-type polysilsesquioxane, caffeic acid and dicyclohexylcarbodiimide described in step B1 is 1:8:8.2, and the usage ratio of the intermediate 3,4-formylphenylboronic acid and 5A molecular sieve is 2mmol:16mmol:2g.

[0020] The amount ratio of the intermediate 4, o-phenylenediamine and potassium carbonate described in step B2 is 1 mmol:8 mmol:1 g, and the molar ratio of the intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 2:1:1.

[0021] The amount of 3-aminopropyltriethoxysilane used in step B3 is 1% of the mass of the precursor. Example 2

[0022] A method for preparing a high-load electrode material comprises the following steps: Step A1: 4,4'-diaminodiphenyl disulfide was dissolved in anhydrous ethanol, and hydrochloric acid solution was added. At a speed of 60 r / min and a temperature of 3°C, sodium nitrite solution was added while stirring. After stirring for 13 minutes, phenol was added and the reaction was carried out for 35 hours. The pH value was adjusted to neutral, the temperature was raised to room temperature, and the mixture was stirred for 2.5 hours to obtain intermediate 1. Step A2: The intermediate 1, epichlorohydrin, benzyltriethylammonium chloride and DMF are mixed uniformly, and the reaction is carried out for 3-4 hours at a speed of 200 r / min, a temperature of 103° C. and nitrogen protection, and the temperature is lowered to 73° C., sodium hydroxide solution is added, and the reaction is continued for 18 hours to obtain the intermediate 2, and the intermediate 2, ethylenediamine and DMF are mixed uniformly, and the reaction is carried out for 9 hours at a speed of 150 r / min, a temperature of 28° C. and a pH value of 12 to obtain the modified monomer; Step A3: Evenly mix the modified monomer, 4,4'4''-triaminotriphenylamine and N-methylpyrrolidone, stir and add 3,3',4,4'-biphenyltetracarboxylic dianhydride at a speed of 120 r / min, a temperature of 25°C and a nitrogen atmosphere, react for 23 hours, add the modified filler, continue stirring for 4 hours, raise the temperature to 183°C, react for 5 hours, and obtain a high-loading electrode material.

[0023] The amount ratio of 4,4'-diaminodiphenyl disulfide, hydrochloric acid solution, sodium nitrite solution and phenol described in step A1 is 2mmol:10mL:5mL:4mmol, the mass fraction of hydrochloric acid solution is 8%, and the mass fraction of sodium nitrite solution is 5%.

[0024] The amount ratio of intermediate 1, epichlorohydrin and sodium hydroxide solution described in step A2 is 40mmol:80mmol:10mL, the mass fraction of sodium hydroxide solution is 30%, the amount of benzyltriethylammonium chloride is 1-3% of the sum of the mass of intermediate 1 and epichlorohydrin, and the molar ratio of intermediate 2 and ethylenediamine is n:n+1, where n is a natural number greater than 0.

[0025] The amount ratio of the modified monomer, 4,4'4''-triaminotriphenylamine, 3,3',4,4'-biphenyltetracarboxylic dianhydride and modified filler described in step A3 is 40mmol:20mmol:60mmol:1g.

[0026] The modified filler is prepared by the following steps: Step B1: octaaminopropyl cage-type polysilsesquioxane, caffeic acid, dicyclohexylcarbodiimide and DMF were mixed evenly, and reacted at a speed of 150 r / min and a temperature of 35° C. for 6 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, 5A molecular sieve and DMF were mixed evenly, and reacted at a speed of 120 r / min and a temperature of 63° C. for 13 h to obtain intermediate 4; Step B2: The intermediate 4, o-phenylenediamine, potassium carbonate and DMF were mixed evenly, reacted at a speed of 150 r / min and a temperature of 83° C. for 13 h, and the pH value was adjusted to 5 to obtain the intermediate 5. The intermediate 5, cobalt nitrate hexahydrate, nickel nitrate hexahydrate and DMF were mixed evenly, ultrasonically treated at a frequency of 25 kHz and a temperature of 23° C. for 35 min, and then allowed to stand for 8 h to obtain the precursor; Step B3: Place the precursor in a tubular furnace, heat it to 850°C at a heating rate of 10°C in a nitrogen atmosphere, calcine for 5 hours, cool it to room temperature, disperse it in anhydrous ethanol, add 3-aminopropyltriethoxysilane and deionized water, react at a speed of 300 r / min and a temperature of 55°C for 2.5 hours to obtain a modified filler.

[0027] The molar ratio of octaaminopropyl cage-type polysilsesquioxane, caffeic acid and dicyclohexylcarbodiimide described in step B1 is 1:8:8.2, and the usage ratio of the intermediate 3,4-formylphenylboronic acid and 5A molecular sieve is 2mmol:16mmol:2g.

[0028] The amount ratio of the intermediate 4, o-phenylenediamine and potassium carbonate described in step B2 is 1 mmol:8 mmol:1 g, and the molar ratio of the intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 2:1:1.

[0029] The amount of 3-aminopropyltriethoxysilane used in step B3 is 2% of the mass of the precursor. Example 3

[0030] A method for preparing a high-load electrode material comprises the following steps: Step A1: 4,4'-diaminodiphenyl disulfide was dissolved in anhydrous ethanol, and hydrochloric acid solution was added. Under the conditions of a rotation speed of 80 r / min and a temperature of 5°C, sodium nitrite solution was added while stirring. After stirring for 15 minutes, phenol was added and the reaction was carried out for 40 hours. The pH value was adjusted to neutral, the temperature was raised to room temperature, and the mixture was stirred for 3 hours to obtain intermediate 1; Step A2: The intermediate 1, epichlorohydrin, benzyltriethylammonium chloride and DMF are mixed uniformly, and the mixture is reacted for 4 hours at a speed of 300 r / min, a temperature of 105° C. and nitrogen protection, and the mixture is cooled to 75° C., a sodium hydroxide solution is added, and the mixture is reacted for 20 hours to obtain the intermediate 2. The intermediate 2, ethylenediamine and DMF are mixed uniformly, and the mixture is reacted for 10 hours at a speed of 200 r / min, a temperature of 30° C. and a pH value of 12 to obtain the modified monomer; Step A3: Evenly mix the modified monomer, 4,4'4''-triaminotriphenylamine and N-methylpyrrolidone, stir and add 3,3',4,4'-biphenyltetracarboxylic dianhydride at a speed of 150 r / min, a temperature of 25°C and a nitrogen atmosphere, react for 25 hours, add the modified filler, continue stirring for 5 hours, raise the temperature to 185°C, and react for 6 hours to obtain a high-loading electrode material.

[0031] The amount ratio of 4,4'-diaminodiphenyl disulfide, hydrochloric acid solution, sodium nitrite solution and phenol described in step A1 is 2mmol:10mL:5mL:4mmol, the mass fraction of hydrochloric acid solution is 8%, and the mass fraction of sodium nitrite solution is 5%.

[0032] The amount ratio of intermediate 1, epichlorohydrin and sodium hydroxide solution described in step A2 is 40mmol:80mmol:10mL, the mass fraction of sodium hydroxide solution is 30%, the amount of benzyltriethylammonium chloride is 1-3% of the sum of the mass of intermediate 1 and epichlorohydrin, and the molar ratio of intermediate 2 and ethylenediamine is n:n+1, where n is a natural number greater than 0.

[0033] The amount ratio of the modified monomer, 4,4'4''-triaminotriphenylamine, 3,3',4,4'-biphenyltetracarboxylic dianhydride and modified filler described in step A3 is 40mmol:20mmol:60mmol:1g.

[0034] The modified filler is prepared by the following steps: Step B1: octaaminopropyl cage-type polysilsesquioxane, caffeic acid, dicyclohexylcarbodiimide and DMF were mixed evenly, and reacted at a speed of 200 r / min and a temperature of 40° C. for 7 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, 5A molecular sieve and DMF were mixed evenly, and reacted at a speed of 150 r / min and a temperature of 65° C. for 15 h to obtain intermediate 4; Step B2: The intermediate 4, o-phenylenediamine, potassium carbonate and DMF were mixed uniformly, reacted at a speed of 200 r / min and a temperature of 85° C. for 15 h, and the pH value was adjusted to 5 to obtain the intermediate 5. The intermediate 5, cobalt nitrate hexahydrate, nickel nitrate hexahydrate and DMF were mixed uniformly, ultrasonically treated at a frequency of 30 kHz and a temperature of 25° C. for 40 min, and then allowed to stand for 9 h to obtain the precursor; Step B3: Place the precursor in a tubular furnace, heat it to 900°C at a heating rate of 10°C in a nitrogen atmosphere, calcine for 6 hours, cool it to room temperature, disperse it in anhydrous ethanol, add 3-aminopropyltriethoxysilane and deionized water, react at a speed of 300 r / min and a temperature of 60°C for 3 hours to obtain a modified filler.

[0035] The molar ratio of octaaminopropyl cage-type polysilsesquioxane, caffeic acid and dicyclohexylcarbodiimide described in step B1 is 1:8:8.2, and the usage ratio of the intermediate 3,4-formylphenylboronic acid and 5A molecular sieve is 2mmol:16mmol:2g.

[0036] The amount ratio of the intermediate 4, o-phenylenediamine and potassium carbonate described in step B2 is 1 mmol:8 mmol:1 g, and the molar ratio of the intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 2:1:1.

[0037] The amount of 3-aminopropyltriethoxysilane used in step B3 is 3% of the mass of the precursor.

[0038] Comparative Example 1 Compared with Example 1, this comparative example uses intermediate 5 instead of precursor, and the remaining steps are the same.

[0039] Comparative Example 2 Compared with Example 1, this comparative example uses octaaminopropyl cage-type polysilsesquioxane instead of the precursor, and the other steps are the same.

[0040] Comparative Example 3 Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.

[0041] The specific capacitance of the electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested at a current density of 1 A / g, and the retention rate of the capacitance value after 5000 cycles was calculated. The results are shown in the following table.

[0042]

[0043] It can be seen from the above table that the present application has a very good capacity, and the capacity decrease is small after multiple cycles.

[0044] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-loading electrode material, characterized in that: The specific steps include: Step A1: dissolving 4,4'-diaminodiphenyl disulfide in anhydrous ethanol, adding hydrochloric acid solution, stirring and adding sodium nitrite solution, stirring, adding phenol, reacting, adjusting the pH value to neutral, stirring, and obtaining intermediate 1; Step A2: Mixing the intermediate 1, epichlorohydrin, benzyltriethylammonium chloride and DMF for reaction, adding sodium hydroxide solution, and continuing the reaction to obtain the intermediate 2, and mixing the intermediate 2, ethylenediamine and DMF for reaction to obtain the modified monomer; Step A3: Mix and stir the modified monomer, 4,4'4''-triaminotriphenylamine and N-methylpyrrolidone, add 3,3',4,4'-biphenyltetracarboxylic dianhydride, react, add the modified filler, continue stirring, and then heat the reaction to obtain a high-loading electrode material.

2. The method for preparing a high-loading electrode material according to claim 1, characterized in that: The amount ratio of 4,4'-diaminodiphenyl disulfide, hydrochloric acid solution, sodium nitrite solution and phenol described in step A1 is 2mmol:10mL:5mL:4mmol.

3. The method for preparing a high-loading electrode material according to claim 1, characterized in that: The amount ratio of intermediate 1, epichlorohydrin and sodium hydroxide solution described in step A2 is 40mmol:80mmol:10mL, the mass fraction of sodium hydroxide solution is 30%, the amount of benzyltriethylammonium chloride is 1-3% of the sum of the mass of intermediate 1 and epichlorohydrin, and the molar ratio of intermediate 2 and ethylenediamine is n:n+1, where n is a natural number greater than 0.

4. The method for preparing a high-loading electrode material according to claim 1, characterized in that: The amount ratio of the modified monomer, 4,4'4''-triaminotriphenylamine, 3,3',4,4'-biphenyltetracarboxylic dianhydride and modified filler described in step A3 is 40mmol:20mmol:60mmol:1g.

5. The method for preparing a high-loading electrode material according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: octaaminopropyl cage-type polysilsesquioxane, caffeic acid, dicyclohexylcarbodiimide and DMF are mixed and reacted to obtain intermediate 3, and intermediate 3, 4-formylphenylboronic acid, 5A molecular sieve and DMF are mixed and reacted to obtain intermediate 4; Step B2: After the intermediate 4, o-phenylenediamine, potassium carbonate and DMF are mixed for reaction, the pH value is adjusted to 5 to obtain the intermediate 5, and the intermediate 5, cobalt nitrate hexahydrate, nickel nitrate hexahydrate and DMF are mixed evenly, ultrasonically treated and then allowed to stand to obtain the precursor; Step B3: placing the precursor in a tube furnace, heating and calcining under a nitrogen atmosphere, cooling to room temperature, dispersing it in anhydrous ethanol, adding 3-aminopropyltriethoxysilane and deionized water, reacting, and obtaining a modified filler.

6. The method for preparing a high-loading electrode material according to claim 5, characterized in that: The molar ratio of octaaminopropyl cage-type polysilsesquioxane, caffeic acid and dicyclohexylcarbodiimide described in step B1 is 1:8:8.2, and the usage ratio of the intermediate 3,4-formylphenylboronic acid and 5A molecular sieve is 2mmol:16mmol:2g.

7. The method for preparing a high-loading electrode material according to claim 5, characterized in that: The amount ratio of the intermediate 4, o-phenylenediamine and potassium carbonate described in step B2 is 1 mmol:8 mmol:1 g, and the molar ratio of the intermediate 5, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 2:1:

1.

8. The method for preparing a high-loading electrode material according to claim 5, characterized in that: The amount of 3-aminopropyltriethoxysilane used in step B3 is 1-3% of the mass of the precursor.

9. A high-loading electrode material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.

Citation Information

Cited By

  • Carbon electrode material for polypyrrole modified bio-based fuel cell and preparation method of carbon electrode material

    CN120589733A